Italian Version of the Scale of Body Connection: Validation and Correlations with the Interpersonal Reactivity Index. (June 2020) - Morganti, Francesca; Rezzonico, Raffaele; Chieh Cheng, Sunny; Price, Cynthia J.
Highlights: The Italian version of the Scale of Body Connection showed adequate internal reliability and construct validity. Convergent validity was demonstrated between the Scale of Body Connection and the Interpersonal Reactivity Index, an empathy measure. The bodily experience of the self appears to be connected to emotional attunement and empathy. The Scale of Body Connection measures the relationship between body and cognition that ground the Self Abstract: In recent years there has been considerable research on body awareness, which is believed to arise from interoceptive and from exteroceptive signals. In addition, body awareness may be related to empathetic disposition during social interaction. In this paper we assess the psychometric properties of the Italian version of the Scale of Body Connection (SBC). We also examine SBC correlations with the Interpersonal Reactivity Index, a measure of empathy. An Italian sample (N = 576) aged from 17 to 72 years old (M = 30.43; sd 9.41) completed these surveys online. The SBC Italian translation was validated by confirmatory factor analysis showing a good model fit. The two-scale SBC factor structure was confirmed. The SBC was positively associated with the Iterpersonal Reactivity Index (IRI), demonstrating convergent validity between these two scales. Specifically SBC-Bodily Dissociation was positively correlated with IRI-Personal Distress subscale and SBC-Body Awareness was positively correlated with IRI-Emotional Concerns, -Fantasy and -Perspective Taking subscales.